ChemInform Abstract: C(sp3)—P versus C(sp2)—P Bond Formation: Catalyst‐Controlled Highly Regioselective Tandem Reaction of Ene‐Yne‐Ketones with H‐Phosphonates. Issue 26 (15th June 2016) - Yu, Yue; Yi, Songjian; Zhu, Chuanle; Hu, Weigao; Gao, Bingjie; Chen, Yang; Wu, Wanqing; Jiang, Huanfeng
Abstract: Various phosphorylated furans are prepared regioselectively via a Cu‐catalyzed C(sp 3 )—P or base‐promoted C(sp 2 )—P bond formation, involving 5‐exo‐dig cyclization, carbene migration insertion, and Michael addition.